Efectividad del programa “Come lo Nuestro” en los conocimientos, actitudes y prácticas sobre el consumo de Quinua, Cañihua y Kiwicha en alumnos del sexto grado de primaria y sus familiares del colegio Adventista Del Titicaca, Puno, Perú, 2007 - Concha Toledo, Manuel (2019)
Objectives: To determine the effectiveness of the program “Eat What is Ours” in knowledge, attitudes and practiceson the consumption of quinoa, cañihua, and amaranth in sixth grade students and their families at the Lake TiticacaAdventist Elementary School, Puno (Peru), 2007. Methodology: A pre-test was applied to 24 students in sixth gradeat the Lake Titicaca Adventist Elementary School: 10 knowledge questions, 13 about attitude, and 6 about practice;a pre-test was applied to the families of these students: 10 knowledge questions, 19 about attitude, and 9 about practices. A promotional educational program was applied which consisted in the use of two modules: one on knowledgeabout the nutritional value of quinoa, cañihua, amaranth and another about motivation for behavior change. Bothmodules were developed in 9 weeks at the end of which a post test was applied to both groups. Results: The resultsshowed that the level of knowledge was higher at the end of the intervention; the attitude was positive and increased consumption practices. Conclusions: The “Eat What is Ours” program had a positive impact on knowledge,attitudes and practices on the consumption of quinoa, cañihua, and amaranth in students from sixth grade and theirfamilies at the Lake Titicaca Adventist Elementary School.